(untitled) (Global Journal of Human-Social Science, 2023)
Bangladesh is aspiring to develop a competitive workforce for the 21st century To reach this aspiration STEM education can be a good way as it has widely been considered to have the potential to prepare students with 21stcentury skills The potentiality of STEM can be fully utilized only when teachers apply STEM approaches effectively in their practices Since teachers prior views and perceptions influence their STEM teaching the study aims to explore the teachers perception of STEM education This study also analyzes the challenges of introducing STEM at primary education in Bangladesh A qualitative research design is adopted in this study Teachers perception of STEM education was explored through semi-structured interviews Additionally in-depth and semi-structured interviews were conducted to examine the challenges of implementing STEM education at the primary level Data were analyzed thematically following an inductive approach One of the key discoveries made in this research is that a large majority of teachers have limited knowledge about STEM education Despite this lack of familiarity it was observed that these teachers occasionally apply the STEM approach unintentionally Most teachers perceive STEM education as effective however it has several challenges to implement such as a lack of teachers knowledge about the discipline and pedagogical approach inadequate physical facilities lack of STEM-related training the mindset of stakeholders etc The findings of the study can be practical guidelines for academic institutions curriculum developers teachers trainers and policymakers